Development of the male generative sphere in Jasminum nudiflorum Lindl. (Oleaceae) - T.N. Kuzmina (Учёные записки Казанского университета: Серия Естественные науки)
To reveal the causes for absence of fruits and seeds in Jasminum nudiflorum Lindl. (Oleaceae) in the Southern Coast of the Crimea, the male generative sphere genesis has been studied and the male gametophyte state during the period of mass blossoming has been determined. The analysis of the permanent preparations of flower buds of J. nudiflorum at different stages of development has demonstrated that the anther wall develops by the centrifugal type. The developed anther wall is formed by epidermis, endothecium, two or three middle layers, and multi-layer tapetum of the secretory type. The sporogenous tissue is represented by two layers of cells. Microsporogenesis is simultaneous. Obliteration of middle layers and tapetum begins at the stage of microsporogenesis. The mature anther of J. nudiflorum contains a three-celled pollen grain and its wall is composed of epidermis covered with cuticle, an irregular two-layered endothecium with fibrous bands. The cytomorphological analysis of the average samples of J. nudiflorum pollen has shown that the proportion of morphologically normal pollen grains makes about 85% during the period of mass blossoming, thereby indicating the genetic stability of this type and the potential ability of the male gametophyte to fertilize efficiently. At the same time, freezing temperatures during the blossoming period of J. nudiflorum affect severely the state of the male gametophyte. The high proportion of morphologically normal pollen grains in J. nudiflorum excludes in the fertility of a male gametophyte a whole number of potential factors influencing the development of seeds in this sort of flowers and provides the grounds for analysis of its generative sphere peculiarities.